Trends of transfusion transmissible infections among blood donors in a rural medical college of West Bengal, India - Kuntala Ray; Hironmoy Roy; Mridumay Das (Al Ameen Medical College, 2018)
Background: Blood transfusion is a life-saving therapy in different medical and surgical emergencies. It also has great public health importance. Objective: The present study was conducted to find out the prevalence of transfusion transmissible infection (TTI) among blood donors, donated blood at the blood bank of North Bengal Medical College, in the reference time period (2008-2014), West Bengal, India. Methods: The Descriptive cross sectional record based study was conducted among all units of blood collected from reference period. The retrospective study was conducted in March-May 2015. All voluntary and replacement donors reporting to the blood bank were screened for HBsAg, Hepatitis C Virus (HCV), HIV and Syphilis by using the appropriate enzyme-linked immunosorbent assay. HIV testing was done using fourth generation ELISA kits. Test for syphilis was done by VDRL. Malaria was tested using Leishman stained peripheral blood smear. Results: A total of 86847 donors donated blood over 7 years, among them 77.3% were males. The sero-positivity for various TTIs was found to be 17.48% for HIV, 42.09% for HBsAg, 25.65% for HCV, 14.52% for syphilis and 0.24% for malarial parasite (MP). Conclusion: Blood is still a main source of transmission of infections among donors in rural West Bengal.